Motivasi dan Fasilitas Kerja sebagai Determinan Kinerja Pegawai pada Puskesmas Kecamatan IX Koto Sungai Lasi Kabupaten Solok - Afni Yeni; Arfimasri Arfimasri; Rivo Fernando (Pusat Riset dan Inovasi Nasional, 2026)
This research was conducted at the IX Koto Sungai Lasi Sub-district Health Center, Solok Regency. The purpose of this study was to determine the influence of motivation and work facilities on employee performance at the IX Koto Sungai Lasi Sub-district Health Center, Solok Regency. A sample of 34 respondents was studied using quantitative methods. The data collection technique used was a questionnaire. Based on a multiple regression analysis of the variables Motivation and Work Facilities on Employee Performance, Y = 7.990 + 0.615 X1 + 0.409 X2 + e. The t-test showed that variable X1, Motivation, significantly impacts Employee Performance, with a calculated t-value of 1.705 > t-table value of 2.03951 and a significance level of 0.098 < 0.05. Therefore, Ha is accepted and H0 is rejected. Variable X2, Work Facilities, significantly impacts Employee Performance, with a calculated t-value of 0.935 > t-table value of 2.03951 and a significance level of 0.357 < 0.05. Therefore, Ha is accepted and H0 is rejected. The F-test showed that Motivation and Work Facilities simultaneously impact Employee Performance, with a calculated f-value of 10.460 > f-table value of 3.30 and a significance level of 0.000 < 0.05. Therefore, H0 is rejected and Ha is accepted.